The Dynamics of Religion and Ecology in Indonesia: An Overview of Environmental Social Movements from 1990-2022 - Ronald Adam; SMith , Jonathan D.; Maarif, Samsul (Jurnal Sosiologi Agama, 2025)
In the longstanding debate over the relationship between religion and ecology, there are two major camps. One side argues that religion contributes to ecological destruction, while the other side argues that religion is a force for saving the environment. Yet both sides tend to view religion as a fixed set of beliefs or practices. This article argues that the relationship between religion and ecology is contested and changing. It provides evidence from an empirical study of how social movements use lived religion, meaning everyday practices instead of doctrines or expert definitions. The study used framework synthesis to select and analyze 244 qualitative studies on Indonesian environmental social movements active between 1990 and 2022, resulting in data about 208 movements spread across 38 provinces. 167 of these movements involved lived religion in some way, leading to four findings about religion and ecology: 1) structural factors influencing social movements to include religion in their ecological responses; 2) dynamic relationship between religion and ecology both within each religious community and throughout history; 3) usefulness of lived religion to show how Indonesian religions and traditions provide resources for environmental movements; and 4) extensive creative responses used by social movements to address environmental crises.